2018
DOI: 10.1097/md.0000000000011135
|View full text |Cite
|
Sign up to set email alerts
|

Can a pulse oxygen saturation of 95% to 96% help predict further vital sign destabilization in school-aged children?

Abstract: To determine whether a peripheral capillary oxygen saturation (SpO2) of 95% to 96% should be considered “nonurgent” in school-aged children, as suggested by the Canadian Emergency Department Triage and Acuity Scale.School-aged children (6–12 years old) with a normal body temperature (36.5–37.4°C) who visited our department between September, 2014 and August, 2015 (n = 4556) were divided into 4 groups based on SpO2: group A: 99% to 100%; group B: 97% to 98%; group C: 95% to 96%; and group D: ≤94%. The heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…In children, average daytime oxygen saturations ≥95% are considered normal, 19 and values below this seen acutely are associated with signs suggesting illness. 20 Overnight medians or means are typically ≥97% in infants 9 , 10 and children, 21 24 rarely dipping to less than 90% in sleep in typically developing children, 21 25 although lower minimum values are seen in normal infants. 10 Nocturnal oxygen desaturation (NOD) is not the norm in infants, children, or adults under the age of 60 years ( Table 1 ).…”
Section: Normal Respiratory Physiology In Sleepmentioning
confidence: 99%
“…In children, average daytime oxygen saturations ≥95% are considered normal, 19 and values below this seen acutely are associated with signs suggesting illness. 20 Overnight medians or means are typically ≥97% in infants 9 , 10 and children, 21 24 rarely dipping to less than 90% in sleep in typically developing children, 21 25 although lower minimum values are seen in normal infants. 10 Nocturnal oxygen desaturation (NOD) is not the norm in infants, children, or adults under the age of 60 years ( Table 1 ).…”
Section: Normal Respiratory Physiology In Sleepmentioning
confidence: 99%
“…[34][35][36] Even within the normoxemia range, children in the general population triaged at the ER with SpO 2 95%-96% compared to 97%-100% had more distress and hospitalization, although outcomes nonetheless remained worse for hypoxemia ≤94%. 37 Normoxemia SpO 2 95%−96% should therefore not be dismissed as nonurgent in a pediatric emergency, and could have implications for SCD when considering a cutoff higher than 95% versus ≥95%. A value such as more than 95% could alternatively be represented as ≥96% to improve clarity and minimize confusion.…”
Section: Discussionmentioning
confidence: 99%
“…Normal values for oxygen saturation tests using pulse oximeters are considered to be 95% or higher. However, in the pediatric setting, it has been suggested that the normal range (at standard altitude) should be considered to be between 97 and 100%, with values of 95% and 96% prompting further investigation to assess whether there is an underlying cause [ 6 , 7 ]. With regards to analyzing pulse oximeter test results, healthcare professionals should be aware that readings may be less accurate in people with dark skin versus light skin.…”
Section: Clinician Perspectivementioning
confidence: 99%